Curta-metragem : gênero discursivo propiciador de práticas multiletradas - Alcântara, Jean Carlos Dourado de (2014)
In view of the growing amount of audio-visual resources that have entered into the school currently, this research aims to reflect about the didactic use of audiovisual language, specifically the short film, by Portuguese teachers in the development of teaching practices. The intention was to discuss not only the pedagogical nature of this tool, but also its potential to produce a transformation in students, making them active subjects in the construction and negotiation of meanings. Through the study of film language, It also sought paths that lead to the valuing and respect to the daily situations, to the diversity and plurality of the students, as specified by the NCP. Our reflections will be based on the experiences of teachers who have used the Short School project, developed by Petrobras since 2006, which provides on its site Brazilian short films. Each short is accompanied by didactic sequences, for use by registered educators. We seek to verify In selected reports, through teaching practices, conceptions of language adopted by teachers, as well as their relationship with the language of cinema and its representative systems. This research is anchored in the enunciation-discursive theory, of social-historical approach, developed by Russian philosopher Mikhail Bakhtin. In addition, we seek, in the light of the cinema theory, understand the process of meaning production of audiovisual language, used in film productions. And, finally, we establish a dialogue between the two theories, in order to determine the dialogic nature also present in film language. To achieve this We applied Bakhtinian categories in the analyze the reports, such as: dialogism, exotopy, surplus of seeing, chronotope etc. After analyzing the data, we concluded that teachers still need training to tackle with the audiovisual language in a enunciative-discursive perspective. Through this research, We intend to contribute for the teachers fill the gap by dealing with cinematic representations.